Aesthetic transfiguration - Pan, Huiting (2014)
In this essay, through the analysis of three novels, John Banville's The Sea, Alessandro Baricco's City and Marcel Proust's In Search ofLost Time, I argue that the aim of art is not to portray the world as it is, but to compose a world aesthetically transfigured, set free from the constraints of the world. In the realm of the aesthetic, our consciousness may be liberated from the constraints of reality and what is impossible in the real world - freedom from the linear causality of time and transcendence from the pain of mortality, as well as liberation from the confines of the self, becomes possible in art. In my essay, I shall analyze works of art in conjunction with the three primary texts as they represent contextual information - the works of Bonnard are directly referenced in Banville and the works of Monet in Baricco, as well as provide the artistic context for my evaluation ofthe writers.